The competencies acquisition with simulation application in the course 'construction planning and controlling'. (2016) - Freire, Ailton Soares; Cavalheiro, Caroline; Ely, Daniela Matschulat; Jungles, Antônio Edésio
This paper presents a report of the table simulation used to develop the students' competencies in the course of 'construction planning and controlling' on a college course of civil engineering at a Brazilian university. The theories used are directly linked to teaching for competence, the methodology of table simulation and planning and controlling of constructions techniques. Two groups of students were compared in the study. One of the groups was submitted to the traditional teaching methodology and the other group to the teaching for competence methodology based on the table simulation technique. The results achieved are: 1) identifying and developing the civil engineer's competencies specialised in construction programming and controlling; 2) confirmation that learning is more effective once it is applied in the student education with exercises and techniques of simulation of professional practice.